Analisis Kesulitan Siswa SMA dalam Memahami Konsep Ikatan Kimia (Systematic Review) - Vonari, Ica Vonari; Sidauruk, Suandi; Asi, Nopriawan Berkat (Jurnal Ilmiah Kanderang Tingang, 2024)
Chemical bonding material has abstract concepts. This research was conducted because there are still many student difficulties in chemical bonding material, so a method of organizing data is needed to describe and summarize student difficulties. This research used systematic review method. The sample in this study used three theses about the difficulties of high school students in understanding the concept of chemical bonds. The data of this research is in the form of student difficulties from the answer patterns and instruments used in each thesis. Instrument analysis in the form of Basic Competencies (KD) and Operational Verbs (KKO) from each thesis while student difficulties are analyzed by comparing student answer patterns. The results of the research on student difficulties in understanding the concept of chemical bonding, namely (1) difficulties in the electron configuration sub-concept are that students cannot determine the stability of elements correctly. Students write the electron configuration out of order and write the atomic number according to the element, (2) the difficulty in the valence electron sub-concept is that students assume the determination of valence electrons based on the number of electrons in the last sub-shell, (3) the difficulty in the ionic bond sub-concept is the lack of student understanding of the properties of metallic and non-metallic elements, (4) the difficulty in the Lewis structure sub-concept is that students assume that by describing just one point it has become one Lewis bond electron pair. Students assume that all atoms that make up the molecule are considered elements, (5) the difficulty in the covalent bond sub-concept is that students assume that the coordination covalent bond is a bond that occurs due to the use of electrons together, and (6) the difficulty in the metal bond sub-concept is that students assume that it is formed between metal and non-metal elements.